Diversification of market for the ukrainian gas turbine building as a key factor of production stabilization in the modern context - Chernova, L. S. (НТУ "ХПІ", 2015)
The article presents the analysis and studying of prospective domestic and external markets for SE ―Zorya‖-―Mashproekt‖ GTR&PC’s products in relation to the current trends of gas turbine industry development in various directions. In addition to the existing markets, in which the products of the above enterprise are present, the prospective alternatives for penetration into the world markets are discussed, as well as participation in the domestic market with consideration for the required diversification not only for SE ―Zorya‖-―Mashproekt‖ GTR&PC, but also for the whole gas turbine industry of Ukraine.

Дана стаття присвячена аналізу та дослідженням перспективних внутрішніх та зовнішніх ринків збуту продукції ДП НВКГ «Зоря»-«Машпроект» у світлі сучасних тенденцій розвитку газотурбінної промисловості за різними напрямками. Розглянуто вже існуючі ринки, де представлена продукція зазначеного підприємства, а також потенційні варіанти для проникнення на світові ринки та участі на внутрішньому ринку з урахуванням необхідної диверсифікації не тільки для ДП НВКГ «Зоря»-«Машпроект», але й для всього газотурбобудування України.
Диверсифікація ринків збуту українського газотурбобудування – ключовий фактор стабілізації виробництва в сучасних умовах
Keywords: diversification of market; gas turbine industry; power generating GTU; general purpose industrial GTE; marine GTE; диверсифікація ринку; газотурбінна промисловість; енергетичні ГТУ; загальнопромислові ГТД